A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana - Almeida, Marlus Queiroz; Salvatierra, Lidianne; de Morais, José Wellington (Zootaxa, 2018)
Mygalomorphs are a diverse spider group with primitive characteristics composed of the largest spider species in the world, however some species may be very small (Bond et al. 2012; Rogerio et al. 2013). The small spiders of the subfamily Masteriinae (Dipluridae, Mygalomorphae) can be found in Asia and South America (Raven 1981; Pedroso et al. 2015; WSC 2017). The subfamily is represented by two genera: Masteria L. Koch, 1873 and Striamea Raven, 1981. Masteria species can be identified by the following combination of characters: absence of cuspules in endites and labium; zero, two, six or eight eyes; and with or without paraembolic apophysis on the male palpal bulb (Raven 1981, 1985, 1991; Alayón 1995; Bertani et al. 2013; Pedroso et al. 2015). Currently, 24 species of Masteria are described, with 6 species found in South America: Masteria colombiensis, Raven, 1981 from Colombia; M. manauara Bertani, Cruz & Oliveira 2013 and M. emboaba Pedroso, Baptista & Bertani, 2015 from Brazil; M. cyclops (Simon 1889), M. tovarensis (Simon, 1889) and M. lucifuga (Simon, 1889) from Venezuela (WSC 2017). We document herein the first record and description of a new species of the genus Masteria from Guyana.